Transfer of radiocaesium (137Cs) to lynx (Lynx lynx) and brown bear (Ursus arctos) in Chernobyl affected areas in Sweden - Chaiko, Yury
In this study, 137Cs activity concentration was measured in 266 lynxes hunted in early spring during the years 2006-2011 in central and northern Sweden and in 161 bears hunted in the end of August until October during the years 2010 and 2011. Highest activity concentrations of 137Cs were observed in lynx and bear coming from counties with highest radiocaesium fallout after the Chernobyl accident. However, activity concentration of 137Cs was higher in the animals of Norrbotten than in Värmland or Dalarna, where average deposition of the Chernobyl was at least threefold higher than that in Norrbotten. Short-term study revealed no temporal trend of 137Cs activity in the studied animals. Compilation of data obtained during this study with original data of 14 years study (1997-2003) conducted by Åhman et al. (2004) shown gradual decline of radiocaesium in lynx. However, the slope of decline varied substantially among the counties. Furthermore, the slope of decline tends to level off in the recent years for all counties. No significant difference was observed in 137Cs activity concentration between males and females of lynx and bear. Age class of lynx found to be a significant factor showing that adults tend to have higher activity concentration of 137Cs than sub-adults. For age class of bear, the results were adverse; sub-adults had higher concentrations than adults did, although the difference was statistically insignificant. Aggregated transfer factor (Tag) was significantly lower in bear compared to lynx, while for both bear and lynx; Tag values were significantly higher in Norrbotten than in rest of the counties. For lynx, Tag values were also significantly higher in Västerbotten than in Dalarna, Gävleborg, Jämtland, Värmland or Västernorrland. Meantime for bear, Dalarna county have shown significantly higher Tag than in Gävleborg, Jämtland, Västerbotten or Västernorrland.